Cognitive and Linguistic Aspects of Using Speech Compression in English–Uzbek Oral Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Speech compression, a vital technique in oral translation, involves condensing source language content while preserving semantic intent, addressing time constraints and cognitive demands in interpreting. This article explores the cognitive and linguistic dimensions of speech compression in English–Uzbek oral translation, a bidirectional process navigating the structural gulf between an analytic Indo-European language and an agglutinative Turkic one. Cognitively, compression taxes working memory and executive functions, balancing efficiency with potential errors, as per Gile’s Effort Model (Gile, 2009). Linguistically, challenges stem from English’s auxiliary-driven syntax versus Uzbek’s suffixal morphology and evidential markers, complicating faithful condensation. Through qualitative analysis and corpus-based examples, this study elucidates strategies like omission, generalization, and syntactic restructuring, drawing on 2024–2025 interpreting research. Findings advocate tailored training for interpreters and enhanced AI translation tools, with implications for multilingual communication in Central Asian contexts.